2022
DOI: 10.1039/d2sc00690a
|View full text |Cite
|
Sign up to set email alerts
|

Photo-modulation of supramolecular polymorphism in the self-assembly of a scissor-shaped azobenzene dyad into nanotoroids and fibers

Abstract: Recent advances in the research field of supramolecularly engineered dye aggregates have enabled the design of simple one-dimensional stacks such as fibers and of closed structures such as nanotoroids (nanorings). More...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 75 publications
(20 reference statements)
0
19
0
Order By: Relevance
“…[2][3][4][5][6][7][8] In some cases, the stabilization energy of the different aggregated states differs only by a few kJ mol À 1 , and they can be isolated under specific conditions in the same solvent, giving rise to supramolecular polymorphs. [22][23][24][25][26][27] For example, the formation of distinct 1D (fibrillar) supramolecular polymorphs with different molecular arrangements has been reported for Pt complexes [24] and PBIs [25] as a function of the sample processing (fast/slow heating-cooling process and sonication, respectively). Similarly, lamellar and fibrillar polymorphs have also been reported for squaraines, [28] PBIs, [29] and barbiturates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4][5][6][7][8] In some cases, the stabilization energy of the different aggregated states differs only by a few kJ mol À 1 , and they can be isolated under specific conditions in the same solvent, giving rise to supramolecular polymorphs. [22][23][24][25][26][27] For example, the formation of distinct 1D (fibrillar) supramolecular polymorphs with different molecular arrangements has been reported for Pt complexes [24] and PBIs [25] as a function of the sample processing (fast/slow heating-cooling process and sonication, respectively). Similarly, lamellar and fibrillar polymorphs have also been reported for squaraines, [28] PBIs, [29] and barbiturates.…”
Section: Introductionmentioning
confidence: 99%
“…[30] However, the interconversion between supramolecular polymorphs is not straightforward, and commonly requires multistep sample processing methods which, in some cases, result in no direct conversion but via intermediate monomeric or kinetic states. [22][23][24][25][26][27][28][29][30] Importantly, since supramolecular polymorphs exhibit different molecular packing, morphology, and/or properties, controlled polymorph transformations are of great interest to develop stimuli-responsive systems. However, direct polymorph transitions are challenging to achieve, particularly in organic solvents where solvophobic effects are attenuated.…”
Section: Introductionmentioning
confidence: 99%
“…This is due to the high kinetic stability of their circular nanostructures without aggregate termini. 42,57,58 Kinetic Studies on the Stacking of Nanotoroids into Nanotubes. Subsequently, we investigated the hierarchical self-assembly of nanotoroids into nanotubes under isothermal conditions.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Here, we report the majority-rules-type amplification of molecular asymmetry shown by scissor-shaped azobenzene dyads that hierarchically organize into well-defined toroidal, tubular, and supercoiled nanostructures. Our previous studies using a series of azobenzene dyad analogues have shown that the hierarchical levels of this system can be accurately controlled by temperature. It has also been shown that the chirality of citronellic-acid-derived side chains, as in 1R and 1S (Figure ), is transferred to supramolecular asymmetry in the different hierarchical levels.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, lamellar and fibrillar polymorphs have also been reported for squaraines, [28] PBIs, [29] and barbiturates [30] . However, the interconversion between supramolecular polymorphs is not straightforward, and commonly requires multistep sample processing methods which, in some cases, result in no direct conversion but via intermediate monomeric or kinetic states [22–30] …”
Section: Introductionmentioning
confidence: 93%